The Translation of Religious Words and Expressions in Naguib Mahfouz’s Sugar - Abdel-Hafiz, Ahmed Sokarno (Technium Social Sciences Journal, 2020)
The translation of culture-specific elements is particularly challenging for translators. Some translators prefer a domesticating strategy, which is characterized by the replacement of foreign cultural elements with TL ones. Other translators opt for a foreignizing strategy, which aims at preserving the values of SL culture. In this day and age, people have become more and more familiar with the cultures of other people. Thus peoples of different countries may share most of the cultural elements: food, clothing, sports, entertainment, etc. Only religion remains resistant to change. Religion is one of the three axes that Mahfouz’s novels revolve around. This study aims at identifying the strategies the translators of Mahfouz’s Sugar Street have employed in rendering religious words and religious expressions. This requires examining both the source text and the target text. Having identified the religious words and expressions in the novel, I traced them in the translated text. It turned out that the translators have used three major types of strategies: foreignizing strategy, domesticating strategy, and a mixture of these two. However, the investigation of these strategies has shown that the foreignizing strategy is the most frequent in the translation of this novel.